Analisis Tindak Pidana Aborsi Dalam Perkara Nomor 482/PID.SUS/2021/PN CKR - Nadya Salsha Tanjung; Hery Firmansyah (UNES Law Review, 2024)
Abortion is a public health problem because it has an impact on maternal morbidity and mortality. As is known, the main causes of death for pregnant women and giving birth are bleeding, infection and eclampsia. However, abortion is actually also a cause of maternal death, only in the form of bleeding complications and sepsis. Abortion, which we often know as the act of aborting a pregnancy, is basically an act that is iprohibited in indonesia. In ithe Criminal Code, regulations regarding abortion are included in the chapter on crimes against life. Criminal responsibility is based on if there is a iviolation of norms and there are sanctions, then there will be responsibility. The iudge in determining criminal responsibility is based on the indictment and the facts in the trial and the fulfillment of the "intentional" element. The basis for the judge's consideration in handing down a decision in the crime of abortion is based on many things, including the evidence presented, the statements of witnesses and the defendant, and the indictment submitted by the public prosecutor.